PSYCHOLOGICAL PREREQUISITES OF EFFECTIVE MASTERING A FOREIGN LANGUAGE FOR SPECIAL OBJECTIVES FOR ADULTS (Pedagogy of Higher and Secondary Education, 2022)
Peculiarities of developing attention, memory and thinking of adult learners are determined in the article and new methods of in telling active lexical minimum are suggested. Work at lexics pi і supposes the introduction o f a special stage o f memorizing the lexical material on the basis o f techniques o f the development of speech mechanisms.